Análisis bacteriológico del arroz con leche expendido en el área metropolitana de Costa Rica - Carranza, Freddy (2013)
Costa Ricans frequently consume  rice pudding that can be prepared either industrially or by artisanal means. In order to evaluate its bacteriological quality, 50 industrial samples and 30 artisanal samples were analyzed.  We considered shelf life, contamination and manipulation indicators, and the presence of potential pathogens, including Staphylococcus aureus, Listeria monocytogenes and Bacillus cereus. We determined the presence of genes (nheA, B and C) for the Bacillus cereus strains using the polymerase chain reaction technique (PCR). 38% of the industrial origin samples and 70% of the artisanal ones showed an aerobic mesophilic total plate count over 104CFU/g, 6% of the industrial samples and 40% of the artisanal ones showed lactic bacteria counts over 104CFU/g. Total coliforms were over 100 MPN/g in 14% of the industrial origin samples, and in 70% of the artisanal ones. Similarly, 8% of industrial samples and 60% or artisanal samples presented a most probable number of fecal coliforms over 100.  Nevertheless, Escherichia coli was only isolated from 6% of industrial samples and 3,3% of artisanal ones. B. cereus was recovered and identified in 8% of the industrial samples and from 13% of the artisanal ones. The presence of genes nheA, B and C was detected in 3 of the strains isolated from industrial samples and all the strains isolated from the artisanal ones. Staphylococcus aureus and Listeria monocytogenes were not isolated.KEY WORDSRice pudding, bacteriological quality, Bacillus cerues, Listeria monocytogenes, nheA, B and C